The transformative power of artificial intelligence in entrepreneurship: exploring AI’s capabilities for the success of entrepreneurial ventures - Yaser Hasan Al-Mamary (Future Business Journal)
Abstract This study examines the influence of artificial intelligence (AI) capabilities on the success of entrepreneurial ventures by enhancing firms’ decision making, automation, customer experience, innovation, risk mitigation and competitive advantage. A quantitative approach was used to gather data from a sample of 327 entrepreneurs through a questionnaire. The collected information was analyzed using structural equation modeling with the SmartPLS software. Additionally, snowball sampling was employed to ensure a diverse sample of entrepreneurs with existing projects. The analysis reveals significant effects of AI capabilities in decision making, innovation, risk mitigation and competitive advantage, all contributing to the success of entrepreneurial ventures. However, automation and customer experience did not show statistically significant effects. The results indicate that entrepreneurs can leverage AI to strategically adopt this technology. Policymakers and investors can use the insights from this work to foster a supportive ecosystem for AI-driven entrepreneurial ventures. Furthermore, the new conceptual framework introduced in this study enhances understanding of how AI can revolutionize entrepreneurship. It also provides valuable insights for entrepreneurs and industry stakeholders operating in AI-driven environments. This study underscores the importance of decision making strategies and the integration of risk reduction practices, ultimately enriching the body of knowledge on AI implementation across various business settings.